Lived experiences of migrant men witnessing and surviving sexual violence in European transit spaces - Leni Linthout; Ilse Derluyn; Caroline Desombre; Massil Benbouriche; Ines Keygnaert (Globalization and Health)
Abstract Background Despite increased scholarly attention to sexual violence, victimization among migrant men and boys remains under researched. This study aims to explore 1) migrant men’s views on and understandings of sexual victimization, 2) their own experiences with surviving and witnessing sexual violence during their past and ongoing migration journeys and 3) the consequences of such victimization and their coping behaviors. Results Participant observation in Brussels (Belgium) and Calais (France) preceded in-depth interviews with 39 migrant men between 16 and 47. Participants varied in age, nationality, educational level and aspired migration projects yet all of them were undocumented. They held varying, yet consistently gendered understandings of sexual violence, depicting women as victims and men as perpetrators. Although they did not explicitly label their own experiences as sexual violence, both direct and indirect forms of it were part of their past and ongoing migration trajectories. Sexual violence had a profound impact on men, inducing shame and challenging their masculine identity. Coping and prevention strategies ranged from normalizing or minimizing the violence and avoidantly forgetting, to protecting one another against future threats. Conclusions The results advocate for safe legal migration routes, increased awareness of migrant men’s vulnerabilities to sexual violence, and enhanced training and screening of professionals and volunteers working in the field.